Developing Omni Channel Financial dan Operational Kalbe pada PT Karya Hasta Dinamika - Ivonne, Ivonne; Karmudiandri, Arwina; Susanto, Yulius Kurnia (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
Merdeka Belajar – Kampus Merdeka (MBKM) provides opportunities for students to gain wider learning experiences and new competencies. The agency where I participated in this internship is PT Karya Hasta Dinamika which focuses on e-commerce for health and fitness products. The responsibility that I have at PT Karya Hasta Dinamika is related to Account Receivable. In addition, I also completed/worked on several cases and projects given by the mentor in the form of making Standard Operating Procedures (SOP), KHD Reports, and Auto Validation Mocha. This report is intended to motivate readers to take part in this internship program in order to increase their knowledge and experience in the world of work. The limitations of this report are the limitations in the attachments provided because of the company's secrets, which must be maintained.